Microwave drying and moisture diffusivity of white mulberry: experimental and mathematical modeling - Evin, Duygu (Korean Soc Mechanical Engineers, 2011)
The literature surveyed revealed that drying kinetics of white mulberry under microwave treatment has not been investigated. In present study, both experimental study and mathematical modeling on microwave drying of white mulberry was performed. The microwave drying process which reduced the moisture content of mulberry from 3.76 to 0.25 (g water/g dry matter) was carried out at 90, 180, 360, 600, and 800 W in a modified microwave drying set-up. The effects of microwave drying technique on the moisture ratio and drying rate of white mulberry were investigated experimentally. Both the effects of microwave power level (under the range of 90-800W) and initial sample weight (50-150g) were studied. No constant rate period was observed. Mathematical modeling of thin layer drying kinetics of white mulberry under microwave treatment was also investigated by fitting the experimental drying data to eight thin layer drying models. Among the models proposed, Midilli et al. model precisely represented the microwave drying behavior of white mulberry with the coefficient of determination higher than 0.999 and mean square of deviation (chi(2)) and root mean square error (RMSE) lower than 1.1x10(-4) and 8.9x10(-3), respectively for all the microwave drying conditions studied. The effective moisture diffusivity (D-eff) of white mulberry varied from 0.45 x 10(-8) to 3.25x10(-8) m(2)s(-1). Both the drying constant (k) and D-eff increased with the increase of microwave power level.
Keywords: Microwave drying kinetics; Moisture diffusivity; Mulberry; Thin layer drying models